Field guide to internal corrosion mitigation and monitoring for pipelines - Eckert, Richard Bruce (NACE International, 2016)
This book is intended to help oil and gas pipeline operators, corrosion professionals, integrity experts, and risk management practitioners assess, control, and manage the effects of internal corrosion on pipeline systems, thus improving the safety, reliability, and integrity of their operations. While the focus of this book is on pipelines, the content is broadly applicable to upstream equipment, processing facilities, mid-stream pipelines, liquid and gas storage assets, and delivery/distribution assets. This book not only provides technical information about internal corrosion control, but also provides suggestions and potential strategies for applying this information. The fundamental process of managing internal corrosion consists of threat assessment, mitigation selection and implementation, and monitoring the effectiveness of mitigation. This book is divided into these three main sections to help emphasize the point that corrosion management is a process, not a one-time event.
Keywords: Pipelines -- Corrosion.; elektronické knihy; electronic books